The Realization of Positive Politeness Strategies on the Tonight Show Starring Jimmy Fallon - Muhammad Zaiim Muhtadi; Hendi Pratama; Abdurrachman Faridi (English Education Journal, 2022)
People communicate with others to complete what is called a ‘social demand’. In conversations, people tend to speak politely to kepp their interlocutors’ feelings so the conversation can be maintained in harmony. They follow several rules and principles that already exist in society. They apply politeness strategies so that the communication can run effectively. This study aims to explain the realization of positive politeness strategies on the tonight show starring Jimmy Fallon. The data were taken from the talk show transcript as the primary source. A descriptive qualitative method was used to analyze positive politeness strategies proposed by Brown and Levinson. Based on the analysis, the positive politeness strategies were used in Jimmy Fallon talk show. The types of positive politeness strategies are are notice (attend to hearer), exaggerate, intensify, use in group identity marker, seek agreement, avoid disagreement, presuppose/assert/raise common ground, joke, assert/presuppose speaker knowledge, offer/promise, be optimistic, include both speaker and hearer in the activity, give/ask for a reason, assume/assert reciprocity, give gifts (sympathy, good, understanding). There were positive politeness strategies used in the utterances with the highest data was performed by the give gifts sub-strategy 12,95%; and the lowest data was performed by assert or presuppose speaker’s knowledge sub-strategy 1,78%. By using positive politeness strategies is expected to show the intimacy relationship among the speaker and interlocutor during the interaction and achieve communicative competence.